2016
DOI: 10.1099/mic.0.000293
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus polysaccharide capsule and Efb-dependent fibrinogen shield act in concert to protect against phagocytosis

Abstract: Staphylococcus aureus has developed many mechanisms to escape from human immune responses. In order to resist phagocytic clearance, S. aureus expresses a polysaccharide capsule, which effectively masks the bacterial surface and surface-associated proteins, such as opsonins, from recognition by phagocytic cells. Additionally, secretion of the Extracellular fibrinogen binding protein (Efb) potently blocks phagocytic uptake of the pathogen. Efb creates a fibrinogen shield surrounding the bacteria by simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 49 publications
0
30
0
2
Order By: Relevance
“…Deletion of the cap genes required for synthesis of the S. epidermidis PGA capsule, causes an increase of S. epidermidis internalization by neutrophils [12]. Other capsular polysaccharides, such as poly-N-acetyl glucosamine (PNAG) also known as polysaccharide intercellular adhesin (PIA) or capsular polysaccharides (CP)5 and CP8, may also protect staphylococci against phagocytosis [54][55][56][57][58]. Since all strains are positive for the for the (icaADBC, cap5, cap8) genes necessary for PNAG/PIA, CP5 and CP8 synthesis, it is unlikely that these capsules are the distinguishing factor in the different level of S. aureus and S. epidermidis internalization by DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the cap genes required for synthesis of the S. epidermidis PGA capsule, causes an increase of S. epidermidis internalization by neutrophils [12]. Other capsular polysaccharides, such as poly-N-acetyl glucosamine (PNAG) also known as polysaccharide intercellular adhesin (PIA) or capsular polysaccharides (CP)5 and CP8, may also protect staphylococci against phagocytosis [54][55][56][57][58]. Since all strains are positive for the for the (icaADBC, cap5, cap8) genes necessary for PNAG/PIA, CP5 and CP8 synthesis, it is unlikely that these capsules are the distinguishing factor in the different level of S. aureus and S. epidermidis internalization by DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Naicker et al reported a strong biofilm formation in ST612 compared to the other clones which may have contributed to its dominance in South Africa [60]. The clone contained only one capsular serotype, cap5, which enhances microbial virulence and offers protection against phagocytic uptake (Figure 2 and Supplementary Table S5) [61]. They also harboured the highly versatile type VII secretion system encoding the eight cluster genes associated with the release of secretions that cause pathogenesis in S. aureus [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Kuipers et al demonstrated that bacterial fibrin formation reduced the innate immune response by inhibiting phagocytosis . Thus, bacterial/fibrin aggregates might be too large to be phagocytized, allowing the bacteria to escape the cells of the innate immune system .…”
Section: Discussionmentioning
confidence: 99%